The Prevalence of Sensitization to Food Allergens from the Group of “Big Eight” in Children with Atopic Phenotype: Cross-Sectional Study - Kamilla E. Efendieva; Julia G. Levina; Vera G. Kalugina; Elena A. Vishneva; Anna A. Alekseeva; Konstantin S. Volkov; Pavel A. Levin; Leyla S. Namazova-Baranova (Педиатрическая фармакология)
Background. Food allergy (FA) is a common chronic disease. There are no official data on the prevalence of FA in Russia. The results of only a few Russian studies of FA and anaphylaxis in children have been published.The aim of the study is to study the prevalence of sensitization to food allergens from the group of “big eight” in children with atopic phenotype living in the Moscow agglomeration.Methods. The cross-sectional study included children aged 0 to 17 years with complaints of seasonal manifestations of allergies / diagnosed with seasonal allergic rhinitis (pollinosis); with complaints of allergic reactions when eating any food; with complaints of atopic dermatitis. The determination of sensitization to allergens was carried out using ImmunoCAP technology, ImmunoCAP ISAC / ALEX2 allergy chips.Results. 240 children were included in the study. Sensitization to extracts of food allergens of the “big eight”, detected by the ImmunoCAP monoplex method, was determined in 1.5 (for fish) — 5 (for wheat) several times more often than with multiplex allergodiagnostics. In molecular allergodiagnosis, sensitization to hazelnut allergens was found in 57%, peanuts — in 47%, soy — in 39%, walnut — in 24%, chicken egg — in 18%, cow’s milk — in 12%, fish — in 9.7%, cashews — in 7.6%, shrimp — in 6.3%, wheat — in 4.6% of children. The frequency of food allergy symptoms, based on the assessment of the patients’ parents, was up to 7 times higher than the detected frequency of sensitization, accompanied by complaints of symptoms when eating the appropriate foods. Among the products causing symptoms in such patients, hazelnuts, cow’s milk, chicken egg and peanuts were in the lead.Conclusion. More than half of Russian children are sensitized to the allergens of the “big eight”, while clinically significant sensitization was noted 2 times less often. Sensitization to the allergen components of the PR-10 group of hazelnuts, peanuts and soybeans was most often detected. The frequency of FA diagnosed by a doctor is significantly lower than the frequency of the disease detected by the results of a survey of patients’ parents.